1068-P: Reassessing Insulin Therapy In Diabetes of the Exocrine Pancreas—A Pilot Study - CICCARELLI, GEA; DI GIUSEPPE, GIANFRANCO; BRUNETTI, MICHELA; SOLDOVIERI, LAURA; DI GIORGI, NICOLETTA; IACOMINI, CHIARA; MASCIOCCHI, CARLOTTA; PATARNELLO, STEFANO; CAPECE, UMBERTO; MORCIANO, CASSANDRA; GUGLIANDOLO, SHAWN; AVOLIO, ADRIANA; et al. (Diabetes (New York, N.Y.), 2024)
Cohort studies have demonstrated that subjects with diabetes of the exocrine pancreas (DEP) are mostly treated with basal bolus insulin. To reassess insulin therapy in subjects affected by DEP, we evaluated the prevalence of insulin therapy in our cohort and investigated the role of other glucose-lowering drugs.We first conducted a retrospective study on DEP subjects referred to our hospital over three years (2021 - 2023). We then conducted an intervention study on 13 subjects with diabetes and acute or chronic pancreatitis, treated with basal bolus insulin. All patients suspended rapid insulin and started a combination of glucose-lowering drugs, chosen according to standard of care. Subjects used a flash glucose monitoring (FGM) system. FGM parameters and quality of life (DQOL) were reported at baseline and after one and three months.We found that 381/490 subjects with DEP were treated with basal bolus insulin. In the intervention study, all subjects had high cardiovascular risk. Basal insulin was titrated during follow-up (10±1 UI vs 16±2 UI; p=0.036) and oral therapy prescribed as follows: metformin 11/13, pioglitazone 5/13, GLP-1RA 3/13, DPP-4i 5/13, SGLT2i 9/13. At one month FGM parameters showed Time In Range (TIR) 64±4 vs 77±7%, Time Above Range (TAR) 35±4 vs 21±8%, Time Below Range (TBR) 1±0.4 vs 1.2±0.7%, Glucose Management Indicator (GMI) 7.2±0.2 vs 6.4±0.2% (p=0.031). At three months we found improved glycemic control (TIR 64±4 vs 86±4%, p=0.009; TAR 35±4 vs 10±8%; p=0.009; TBR 1±0.4 vs 1±0.6% ns; GMI 7.2±0.2 vs 6.1±0.3%; p=0.042) and quality of life (2.5±0.6 vs 1.3±0.6; p=0.041). No DKA or acute pancreatitis recurrence occurred. Combination of basal insulin and oral glucose-lowering drugs significantly improved glycemic control and quality of life compared to basal-bolus insulin therapy. Therapies used in type 2 diabetes may be useful in DEP to improve metabolic control and reduce cardiovascular risk. Larger studies are warranted to assess safety and efficacy of these drugs in DEP.